Probiotic composition for nutraceutical product. - Foo, Hooi Ling; Loh, Teck Chwen; Abdul Rahim, Raha; Lim, Yin Sze (2009)

(untitled)
The present invention relates a naturally occurring source of metabolites produced by a probiotic bacterial spp and a method of using the probiotic as a dietary supplement. Also, the present invention relates to nutraceutical product(s) including bacteriocins and organic acids, such as formic, acetic acid and lactic acid. The present invention also has the ability to inhibit various food-borne pathogens and also offers health promoting effect of reduction in serum cholesterol level is another aspect of the present invention.